A tale of two city-states: Novgorod and Pskov in the 1990s - Laura Solanko; Merja Tekoniemi (Bank of Finland, Institute for Economies in Transition (BOFIT), 2000)
This paper examines two regions of the Russian Federation, Novgorod and Pskov, to compare how differences in economic policy affect economic development.Despite common histories, geography and natural resources, Novgorod committed early on to policies that would attract foreign investments in production.Pskov, on the other hand, withdrew into protectionist policies until it was clear that efforts to increase domestic and foreign investment levels were needed.Using available statistics, we consider the reasoning that led these regions down such distinctly different economic policy paths and consequences of these choices.
URN:NBN:fi:bof-201408072202
Keywords: 330; Russia; regions; Novgorod; Pskov